Evaluasi Karakteristik dan Tingkat Kematian Gulma Tali Susu (Merremia peltata) dengan Bahan Aktif Metil metsulfuron dan Parakuat diklorida di Perkebunan kelapa Sawit - Sylvia Madusari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The purpose of this research is to analyze the characteristics of physical changes of weeds of Merremia peltata and the level of herbicide of methyl metsulfuron and paraquat dichloride in controlling the weeds in oil palm plantations. The method used in the implementation of this research was descriptive method by observing physical changes occurring on the leaves, stems and mortality rate of the weeds at a maximum time interval of 25 days. The study was divided into two groups, ie the weeds were treated with the active ingredient methyl metsulfuron and the weeds were treated with the active ingredient paraquat dichloride. At the treatment of methyl metsulfuron consists of 5 concentration, that was: 1) concentration of 2.5 g/12 liters of water; 2) concentration of 3.5 g/12 liters of water; 3) concentration of 4.5 g/12 liters of water; 4) concentration 5.5. gr/12 liters of water; and 5) concentration of 6.5 gr/12 liters of water. The treatment of the active ingredient paraquat dichloride consists of 3 concentrations, namely: 1) 60 ml/15 liters of water; 2) 70 ml/15 liters of water; and 3) 80 ml/liter of water. The results showed that changes in leaves and stems began to appear on day 3 after application and at the end of observation of active ingredient Methyl metsulfuron killed the weeds with concentrations of 6.5 gr/12 liters of water. Meanwhile, the paraquat dichoride active ingredients gave initial changes to the leaves and stems on day 1 after application and killed th weeds with concentrations of 80 ml/15 liters of water. At the end of the observation, both active ingredients were capable kill the weeds and showed no visible signs of regrowth and no new shoots appeared.